Pasting and reversing approach to matrix theory (2016)
The aim of this paper is to study some aspects of matrix theory through pasting and reversing using linear mappings. We obtain new properties and new sets in matrix theory. In particular, we introduce new linear mappings: palindromicing and antipalindromicing mappings, which allow us to obtain palindromic and antipalindromic vectors and matrices.